2017
DOI: 10.1177/0271678x17720816
|View full text |Cite
|
Sign up to set email alerts
|

Occludin regulates glucose uptake and ATP production in pericytes by influencing AMP-activated protein kinase activity

Abstract: Energetic regulation at the blood-brain barrier is critical for maintaining its integrity, transport capabilities, and brain demands for glucose. However, the underlying mechanisms that regulate these processes are still poorly explored. We recently characterized the protein occludin as a NADH oxidase and demonstrated its influence on the expression and activation of the histone deacetylase SIRT-1. Because SIRT-1 works in concert with AMP-activated protein kinase (AMPK) (AMPK), we investigated the impact of oc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(54 citation statements)
references
References 70 publications
2
47
0
Order By: Relevance
“…52 Modification of the cav-1-ocln-Alix complex by overexpression of ocln also resulted in a prominent decrease in p24 levels in HIV-1-infected pericyte cultures ( Figure 6). These findings are consistent with our reports 25 in which we characterized ocln as a novel NADH oxidase that inhibits HIV-1 transcription by controlling SIRT-1 expression and activation in human brain pericytes. The inverse relationship between ocln and HIV-1 transcription was further substantiated when it was shown that occludin silencing resulted in 75% and 250% increase in viral transcription in human primary macrophages and differentiated monocytic U937 cells, respectively.…”
supporting
confidence: 93%
See 1 more Smart Citation
“…52 Modification of the cav-1-ocln-Alix complex by overexpression of ocln also resulted in a prominent decrease in p24 levels in HIV-1-infected pericyte cultures ( Figure 6). These findings are consistent with our reports 25 in which we characterized ocln as a novel NADH oxidase that inhibits HIV-1 transcription by controlling SIRT-1 expression and activation in human brain pericytes. The inverse relationship between ocln and HIV-1 transcription was further substantiated when it was shown that occludin silencing resulted in 75% and 250% increase in viral transcription in human primary macrophages and differentiated monocytic U937 cells, respectively.…”
supporting
confidence: 93%
“…[20][21][22] Occludin (ocln) is a transmembrane TJ protein 24 ; however, recent evidence has shown an important role of this protein in regulating cellular metabolism through influencing AMPK protein kinase activity, ATP production, and glucose uptake. 25 Importantly, ocln can control the responses of human pericytes to HIV-1 and influence the level of infection. 20 Another membrane protein that is involved both in maintaining BBB integrity and HIV-1 infection is caveolin-1 (cav-1).…”
mentioning
confidence: 99%
“…Furthermore, astrocytes and pericytes express comparable amounts of GLUT1 and GLUT4 (Castro et al . ).…”
Section: The Role Of Non‐neuronal Cells In Brain Energy Metabolismmentioning
confidence: 97%
“…for both GLUT1 and GLUT4 are detectable in human and murine brain pericytes (Castro et al, 2018;He et al, 2018;Vanlandewijck et al, 2018), indicating that glucose uptake can occur via both insulin-dependent and independent pathways. This may explain the greater maximum glucose transport capacity observed in bovine retinal pericytes as compared to endothelial cells (which uptake glucose exclusively through GLUT1) (Mandarino et al, 1994).…”
Section: Metabolic Support Of Pericyte Statusmentioning
confidence: 99%